Simulation of temperature distribution in double-row potato ridges mulched with plastic film covered with soil - Liu, Quandong; Sun, Wei; Wang, Yongmei; Wang, Juanling; Che, Xinglong (International Journal of Agricultural and Biological Engineering, 2024)
In Northwest China, potatoes are cultivated on double-rows of each ridge which is mulched with plastic film, and the film is covered with some of soil. While effective in retaining soil moisture, this technique can render the potato seedlings prone to be burned if they are not released from the plastic film in time. In this study, the model of convective heat transfer of potato ridge under solar radiation and atmospheric radiation is established by the Fluent software. The processes of the heat transfer of potato ridge was simulated for a certain day, and the temperature distribution in the potato ridge was monitored over time. The temperature distribution of soil in the growth layer of potato plants was analyzed under different thickness and widths of the covering soil on the film. The results showed that with the increase of covering soil thickness and width, the time for soil at different depth to reach the peak-temperature was delayed, and the daily temperature change of soil where the different depths layer of potato plants growth was reduced. At that time, a binary regression equation of offset temperature was constructed by using the Response Surface Method. The best parameter combination for covering soil on the plastic film is a thickness of 50 mm and a width of 280 mm in the cold and arid areas of Northwest China. However, the offset temperature (PT) first decreased and then almost remained unchanged with the increase of covering soil thickness. Considering the operational efficiency and power consumption of soil covering devices in the field, the unchanged width of the covering soil is 200 mm. The field experiments have shown that a 50 mm thick of soil covering is beneficial for the growth of potato plants and a 200 mm width of soil covering is beneficial for the growth of potato plants. The height of potato plants was 21 cm, and the natural emergence rate of potatoes was 95.8% on June 9, 2024. The environment of soil covered could provide theoretical support for the mechanized planting of potatoes. Key words: potato growth; plastic mulching; soil covered with film; temperature distribution; natural emergence rateDOI: 10.25165/j.ijabe.20241704.8357Citation: Liu Q D, Sun W, Wang Y M, Wang J L, Che X L. Simulation of temperature distribution in double-row potato ridges mulched with plastic film covered with soil. Int J Agric & Biol Eng, 2024; 17(4): 185–197.